A Conceptual Replication Study of the Enhanced Core Reading Instruction MTSS-Reading Model. (April 2021) - Fien, Hank; Nelson, Nancy J.; Smolkowski, Keith; Kosty, Derek; Pilger, Marissa; Baker, Scott King; Smith, Jean Louise Mercier
States are increasingly recommending that districts and schools use multi-tiered systems of support (MTSS) to improve reading outcomes for all students. States have also suggested MTSS is a viable service delivery model in response to new state legislation to screen, identify, and treat students with word-level reading disability (i.e., dyslexia). One model of MTSS that utilizes Enhanced Core Reading Instruction (ECRI MTSS), has demonstrated significant increases in students' early acquisition of foundational reading skills (Smith et al., 2016). The purpose of this study was to conduct a conceptual replication of the Smith's (2016) original impact study. In a cluster-randomized controlled trial, 44 schools were randomly assigned to the ECRI MTSS treatment or a business-as-usual (BAU) MTSS control condition. Across conditions, 754 students were assigned to receive Tier 2 intervention in addition to Tier 1 instruction. Impact data indicate moderate to strong effects on student decoding, word reading, and fluency skills for students in the ECRI MTSS schools. Results suggest that schools can use ECRI MTSS to improve foundational reading skills for struggling early readers, including students with or at risk for word-level reading disabilities (i.e., dyslexia).